KEMATIAN, MONUMEN KUBUR, DAN PELAPISAN SOSIAL MASYARAKAT DI SUMBA TIMUR - Diman Suryanto (BRIN, 2003)
The social status of a person can be seen from the ceremonies that are held at the time of death, besides it can also be seen from the shape of their burials. Through descriptive oservations, it can also be distinguished between ornate and unadorned reti. Common decorations include animal decorative patterns, for example buffalo, turtles, lizards and some human decorative patterns. This decorative pattern is found on the front and back of the supported stone. Most buffalo decorative patterns depict the head complete with horns, but sometimes just horns. This decorative pattern of buffalo, turtles and lizards was found in Paraiyawang village (Rindiumaluju). In addition to the decorative patterns mentioned above, there are also circle decorative patterns, tumpal decoration, for example found in Lambanapu village (Paraliu sub-district).